Effect on Pulmonary Atery Presssres after Transcatheter Occlusion of Patent Ductus Arteriosus with Severe Pulmonary Artery Hypertension - Aurangzeb, Abdul Sattar Sheikh, Muhammad Asif Khan, Hussain Bux, Veena Kumara, Shah Nawaz Sathio, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to ascertain how the patent ductus arteriosus will respond to trans catheter closure on the pulmonary artery pressure. Methods: All patients having clinical and echocardiographic evidence of hemodynamically significant isolated PDA and patients with PASP > 20 mmHg will be labelled as PDA with PAH, while patients with mean PASP > 60 mmHg will be labelled as PDA with severe PAH. These patients were all included in the research. Both pulmonary artery pressure measurements and echocardiography were done. Once the patient has been assessed, the viability of a transcatheter closure PDA has been confirmed. Results: The Mean age of the patients were 10.6±8.18 years. Out 40 participants 35% were males and 65% were females. A significant variation (p=0.003) in MPA pressure was observed in patients after balloon occlusion. A significant variation in RV higher (0.007) and lower (0.003) pressure was observed in patients after balloon occlusion. A significant variation (p=0.005) in LV Higher pressure was observed in patients after balloon occlusion. A significant variation (p=0.003) in higher Aorta pressure was observed in patients after balloon occlusion. Conclusion: After PDA closure, some individuals with borderline hemodynamic data with PDA and PAH may get worse or continue to have PAH. Care must be taken while providing these individuals with permanent closure.